Effectiveness of the Lace Method in Osteosynthesis for Hand Fractures in the Kyrgyz Republic (Asian Journal of Pharmaceutics (AJP), 2024)
Introduction: Hand fracture management remains complex, with treatment approaches varying based on fracturetype, patient characteristics, and healthcare system constraints. Objectives: This retrospective study aimed todetermine the effectiveness of the lace method of osteosynthesis in the Kyrgyz Republic and the anesthetic aspectsof this method. Materials and Methods: Patients aged 3–71 years with confirmed wrist fractures were dividedinto two groups: Group 1 (n = 90) underwent cord osteosynthesis, while Group 2 (n = 34) received standardosteosynthesis treatment. The study compared general and administrative indicators of medical care qualitybetween the groups. Results: Domestic injuries were prevalent in all groups and categories, while work injurieshad a more stable distribution. Conductor cells accounted for the majority of anesthesia types in both groups(42.20% in Group 1 and 50.00% in Group 2). Group 1 had a higher percentage of local and general anesthesia,whereas Group 2 had a higher content of conductive anesthesia. The age distribution differed between thegroups, with Group 1 primarily composed of children of primary and secondary school age, while Group 2 had ahigher proportion of adults aged 18–50 years. Conclusion: The findings suggest differences in the compositionof anesthesia used and age distribution between the two groups, which may have implications for treatmentoutcomes and functional activity. Further research is needed to establish standardized guidelines for hand fracturemanagement and to evaluate the effectiveness of the lace method of osteosynthesis in various patient populations.